Incorporation of Amphipathic Diblock Copolymer in Lipid Bilayer for Improving pH Responsiveness - Tian Xia; Weiju Hao; Yazhuo Shang; Shouhong Xu; Honglai Liu (International Journal of Polymer Science)
Diblock copolymers (mPEG-b-PDPA), which were designed to possess pH-sensitivity as well as amphipathy, were used as an intelligent lock in the liposomal membrane. The so-called pH-sensitive liposomes were prepared by simple mixing of the synthesized mPEG-b-PDPA with phospholipids and cholesterol. Fluorescence polarization at pH 7.4 showed that the membrane stability of the hybrid liposome was significantly increased compared with the pure liposome. Therefore, in the neutral environment, the leakage of doxorubicin (DOX) was inhibited. However, when pH decreased to 6.0, DOX release rate increased by 60% due to the escape of copolymer. The effects of the membrane composition and the PDPA segment length on bilayer membrane functions were investigated. These results revealed that the synthesized copolymers increased the difference in DOX cumulative release between pH 7.4 and 6.0, that is, improved the pH-controllability of the drug release from hybrid liposomes.